Prevalence of hypothyroidism in patients with type 2 diabetes mellitus attending a tertiary care hospital in a rural area of Bihar, India - Kamendu, Abhishek; Aslami, Ahmad Nadeem (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes has become a major health challenge all over the world. Previous studies have found that diabetes and thyroid disorders mutually influence each other and both disorders tend to coexist. The aim of this study was to find out prevalence of hypothyroidism and its associated factors in type 2 diabetes mellitus patients. Methods: Consecutive 200 patients with type 2 diabetes mellitus attending outpatient department of medicine in a tertiary care centre in Sasaram, Bihar were evaluated clinically and biochemically. Subclinical hypothyroid and overt hypothyroidism was diagnosed as per standard definitions. The results obtained were statistically analysed by using chi square test and finding odds ratio. Results: Out of 200 patients, 75.5% were euthyroid while 24.5% were hypothyroid. Out of 49 hypothyroid patients, subclinical hypothyroid (SC-Hypo) was present in 41 patients and overt hypothyroid (C-Hypo) was present in only 8 patients. The prevalence of hypothyroidism was found more in males, age ≥60 years, patients with HbA1c value ≥7%, patients with diabetes duration less than 5 years and in hypertensive patients. Conclusions: Thyroid dysfunction screening should be done in all type 2 diabetic patients periodically and appropriate individualized treatments in addition to thyroid function test should be given to diabetes mellitus patients with subclinical hypothyroidism as well.